ANTIBODIES TO INFLUENZA A VIRUS IN LESSER (AYTHYA AFFINIS) AND GREATER SCAUP (AYTHYA MARILA) IN THE USA - Harrison Huang; Rebecca L. Poulson; Jeffery D. Sullivan; Susan E. W. De La Cruz; Hutchison Walbridge; David E. Stallknecht; Diann J. Prosser (Journal of Wildlife Diseases, 2024)
Scaup, including both Lesser and Greater (Aythya affinis and Aythya marila, respectively), are a grouping of populous and widespread North American diving ducks. Few influenza type A viruses (IAV) have been reported from these species despite a high prevalence of antibodies to IAV being reported. Existing virologic and serologic data indicate that IAV infection routinely occurs in scaup, yet it is unknown which IAV subtypes are linked to these infections. In this study, we aimed to gain a more complete picture of IAV natural history in Lesser and Greater Scaup from two coastal flyways in North America in 2015–18 (302 samples from California in the Pacific Flyway and 471 samples from Maryland in the Atlantic Flyway). Low prevalence of active IAV infection was detected by real-time reverse-transcription PCR in Lesser Scaup sampled in Maryland and California (2.8% and 8.1%, respectively). A single IAV (H1N1) was isolated in embryonated chicken eggs from a bird sampled in California. Similarly low levels were observed in Greater Scaup in California (3.3%). Antibodies to the nucleoprotein as detected with a commercial blocking ELISA were observed in all species and flyway combinations. Antibody seroprevalence estimates were higher in adult Lesser Scaup than in juveniles at both the ≤0.5 (P<0.001, z=–3.582) and ≤0.7 serum-sample-to-negative-control absorbance thresholds (P=0.003, z=–2.996). Neutralizing antibodies to H1–H12, H14, and H15 were detected using a microtiter virus neutralization assay, with the highest prevalence of antibodies against H1 (38%), H6 (36%), and H11 (35%). The high prevalence of antibodies to IAV and evidence of previous exposure to numerous subtypes are consistent with a high level of population immunity and a low prevalence of infection. These results must be interpreted in the context of season (winter sampling), as results may vary with the annual influx of naïve juvenile birds.